Investment Knowledge, Risk Perception, Technology Advances, and Investment Interest of Z-Generation - devy, happy sista; Syamsuddin, Syamsuddin; Rahmawati, Nor Fatmah; Zahra, Fatima (Jurnal Manajemen dan Keuangan, 2023)
This study aimed to determine the effect of investment knowledge , and risk perception on investment interest , and determine whether technological advances can moderate their influence. This study uses a population of all students of the Faculty of Economics in the Provinces of Central Java, West Java, East Java, and the Special Region of Yogyakarta they were born in 1998-2003. Data analysis uses the E-views application by analyzing the validity, reliability, classical assumptions, regression analysis , and moderated testing. The results of this study indicate that the more you have adequate knowledge, especially on stock indexation, one of which is IDX-MES BUMN 17, the higher the interest in investing in the capital market. The existing technological advances are can also moderate the effect of investment knowledge , and risk perception on investment interest. If the desired increase in investment interest is in the advancement of the Islamic capital market, especially among Z-generation, then what needs to be improved